Postoperative neutrophil-to-lymphocyte ratio predicts malignant cerebral edema following endovascular treatment for acute ischemic stroke - Zheng, Sujie; Jiang, Xinzhao; Guo, Shunyuan; Shi, Zongjie (Frontiers in Neurology, 2024)
Background and purpose Malignant cerebral edema (MCE) is one of serious complications with high mortality following endovascular treatment (EVT) for acute ischemic stroke (AIS) with large vessel occlusion. We aimed to investigate the relationship between postoperative neutrophil-to-lymphocyte ratio (NLR) and MCE after EVT. Methods The clinical and imaging data of 175 patients with AIS of anterior circulation after EVT were studied. Admission and postoperative NLR were determined. The presence of MCE was evaluated on the computed tomography performed 24 h following EVT. The clinical outcomes were measured using the modified Rankin Scale (mRS) at 90-day after onset. Univariate and multivariate regression analyses were used to analyze the relationship between postoperative NLR and MCE. Optimal cutoff values of postoperative NLR to predict MCE were defined using receiver operating characteristic analysis. Results MCE was observed in 24% of the patients who underwent EVT and was associated with a lower rate of favorable clinical outcomes at 90-day. Multivariate logistic regression analysis demonstrated that baseline Alberta Stroke Program Early CT Score (ASPECT) score (OR = 0.614, 95% CI 0.502–0.750, p = 0.001), serum glucose (OR = 1.181, 95% CI 1.015–1.374, p = 0.031), and postoperative NLR (OR = 1.043, 95% CI 1.002–1.086, p = 0.041) were independently associated with MCE following EVT for AIS with large vessel occlusion. Postoperative NLR had an area under the receiver operating characteristic curve of 0.743 for prediction MCE, and the optimal cutoff value was 6.15, with a sensitivity and specificity of 86.8% and 55%. Conclusion Elevated postoperative NLR is independently associated with malignant brain edema following EVT for AIS with large vessel occlusion, and may serve as an early predictive indicator for MCE after EVT.